Transgenic Approaches to Develop Abiotic Stress Tolerant Crop Plants: Rice as the Model Example - Satya, P.; Mitra, J.; Kar, C. S.; Sharma, H. K. (International Journal of Bio-resource and Stress Management, 2010)
Abiotic stress is a major limiting factor for crop productivity. The nature and extent of abiotic stress on crop plants are rapidly increasing with destabilization of environmental balance and deterioration of soil productivity. Transgenic approach has the potential of introducing specific genes from stress tolerant plant species in major crops. Rice is the principal food grain crop for more than half of the world population and faces different kinds of stresses in varying environments. No other crop species is grown in diverse ecology as in case of rice. Being one of the model plant for transgenic research and a premier crop species, it has been targeted several times for development of transgenic genotypes having resistance to salinity, drought, cold, or nutritional stresses. Several path breaking achievements have been made in this exciting research area in recent years, which is discussed here.